2016
DOI: 10.1007/s11604-016-0584-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimized workflow and imaging protocols for whole-body oncologic PET/MRI

Abstract: Although PET/MRI has the advantages of a simultaneous acquisition of PET and MRI, high soft-tissue contrast of the MRI images, and reduction of radiation exposure, its low profitability and long acquisition time are significant problems in clinical settings. Thus, MRI protocols that meet oncological purposes need to be used in order to reduce examination time while securing detectability. Currently, half-Fourier acquisition single-shot turbo spin echo and 3D-T1 volumetric interpolated breath-hold examination m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This adopted time efficient PET/MRI whole-body protocol and regional study as per clinical need is similar to reported earlier[ 5 6 ] but were different in terms of MR sequence type along with selective imaging planes.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This adopted time efficient PET/MRI whole-body protocol and regional study as per clinical need is similar to reported earlier[ 5 6 ] but were different in terms of MR sequence type along with selective imaging planes.…”
Section: Resultsmentioning
confidence: 93%
“…The present protocol acquires images in axial orientation to cover the whole body in matching slices with optimized T1 TFL sequence for T1 contrast, STIR for T2 contrast, diffusion (with different b values), and fat-suppressed postcontrast (VIBE) images in addition to PET for spatial correlation of tissue parameters to assess the nature of a lesion which is distinct from reported by others. [ 5 6 ] Such an approach greatly helps in the correct classification of a nonmetastatic marrow lesion from a true metastatic one as seen in Figure 3 , thus improving staging accuracy impacting clinical management. Acquiring in the axial plane through optimized sequences avoided bias induced in the localization of lesions when images are read in rather different planes with an objective to reduce imaging time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, no contrast agent was used and the addition of SPAIR did not significantly affect SNR and contrast between tumours, LN, and surrounding tissue. Nevertheless, unenhanced T2-HASTE sequences have been reported to sensitively detect pleural effusion and intra-atelectatic tumour growth [9,20,21]. The effect of motion and MR motion-correction was less prone on PET-images, although motion has a negative effect on the localisation of PET-signal.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in semiconductor photon detection devices, integrated PET-MRI has been developed and implemented as a clinical scanner. 15 The MR-specific research area is relatively limited; however, interesting studies have been conducted, including pseudo-CT image synthesis from MR images for attenuation correction, 16 , 17 lung imaging with zero TE, 18 arterial spin labeling cross-validation, 19 and whole-body diffusion cross-validation with PET imaging. On the other hand, a PET detector insert combined with MRI transmit and receive coil system has been developed.…”
Section: Mr System Developmentmentioning
confidence: 99%